2019
DOI: 10.1021/acs.inorgchem.9b02718
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Electronic Structures of μ-Oxo, μ-Nitrido, and μ-Carbido Diiron Octapropylporphyrazine Complexes and Their Catalytic Activity in Cyclopropanation of Olefins

Abstract: The electronic structure of three single atom bridged diiron octapropylporphyrazine complexes (FePzPr8)2X having Fe(III)-O-Fe(III), Fe(III)-N-Fe(IV) and Fe(IV)-C-Fe(IV) structural units was investigated by Mössbauer spectroscopy and DFT calculations. In this series, the isomer shift values decrease whereas the values of quadrupole splitting become progressively greater indicating the increase of covalency of Fe-X bond in the µ-oxo -µ-nitrido -µ-carbido row.The Mössbauer data point to low spin systems for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 107 publications
0
20
0
Order By: Relevance
“…It is of interest to study the role of the single-atom bridging group. To this aim, the structural and electronic Mössbauer study and DFT calculations indicated the increase of covalency of Fe-X bond in the µ-oxo → µ-nitrido → µ-carbido row and their low-spin character, a singlet state for µ-oxo and µ-carbido and a doublet state for µ-nitrido [85]. These complexes catalyze cyclopropanation of styrene and its derivatives with 0.1 mol% loading and 1.2 equiv ethyl diazoacetate (EDA).…”
Section: µ-Oxo Complexesmentioning
confidence: 98%
See 1 more Smart Citation
“…It is of interest to study the role of the single-atom bridging group. To this aim, the structural and electronic Mössbauer study and DFT calculations indicated the increase of covalency of Fe-X bond in the µ-oxo → µ-nitrido → µ-carbido row and their low-spin character, a singlet state for µ-oxo and µ-carbido and a doublet state for µ-nitrido [85]. These complexes catalyze cyclopropanation of styrene and its derivatives with 0.1 mol% loading and 1.2 equiv ethyl diazoacetate (EDA).…”
Section: µ-Oxo Complexesmentioning
confidence: 98%
“…While µ-nitrido and µ-carbido carbene complexes have LUMOs localized on * orbitals of the distal Pz ligand, LUMO of the µ-O species is the unoccupied  2py orbital of the radical carbon atom of carbene species (Fig. 27) [85]. This difference in electronic structures can explain the superior activity of µ-O-based species and lower reactivity of µ-C and µ-N entities.…”
Section: µ-Oxo Complexesmentioning
confidence: 99%
“…In light of Lever’s work and the considerable academic and industrial interest surrounding iron phthalocyanine (PcFe II ) derivatives, this work focuses on expanding the already rich chemistry of these complexes. Indeed, iron phthalocyanine complexes have been studied as catalysts for C–H bond activation, electrocatalysts for the oxygen reduction reaction, active components for catalytic cancer therapy, , platforms for optical detection of small molecules, and composite materials for electrochemical detection of biologically relevant species. The axial coordination of nitrogen bases, phosphines and phosphites, nitroso compounds, sulfoxides and sulfides, carbon monoxide, and isonitriles to iron­(II) phthalocyanine was studied by UV–visible, NMR, and Mössbauer spectroscopies as well as by crystallography. Based on early electrochemical, spectroelectrochemical, chemical, , and photochemical oxidation data, it was always assumed that the highest occupied m...…”
Section: Introductionmentioning
confidence: 99%
“…The positive ρ values with σ polar substituent constants (ρ P = 0.83 and ρ P – = 0.55) indicate the formation of a negatively charged transition state at the rate-determining step and rule out a dominant contribution of the radical-based mechanism. To take into account both the polar effect (ρ X σ X ) and the spin-delocalization effect (ρ • σ • ) of the substituents, we employed a dual-parameter equation [log k obs = ρ X σ X + ρ • σ • ]. , Plotting the data with the Hammett σ P substituent constant and Creary’s σ C • spin-delocalization substituent constant in a multiple linear regression provides ρ P and ρ C • values of +0.65 and +0.09, respectively, with the a significantly improved linear correlation ( R 2 = 0.97) as well as the result using Jiang’s σ mb polar substituent constant and σ JJ • spin-delocalization substituent constant (ρ mb = +0.62, ρ JJ • = +0.08, R 2 = 0.92) (Figures cd). The large |ρ X /ρ • | ratios of 7.2 (ρ P /ρ C • ) and 7.8 (ρ mb /ρ JJ • ) indicate that the polar effect is dominant in the reductive debromination reaction of benzyl bromide by rMb­(Ni I (TDHC)).…”
Section: Resultsmentioning
confidence: 99%